The 2D Educational Game Prevention of Covid-19 in Indonesia - Sudarmilah, Endah; Mulyana, Afrizal Meka (Universitas Pendidikan Ganesha, 2022)
The emergence of a corona virus called Covid-19, has caused a pandemic throughout the world, especially Indonesia. Many people do not understand about this virus. The game, which was developed with 2D-based Construct 3, is expected to attract more users’ attention to learn about Covid-19, such as Symptoms, History, Health Protocols, and Vaccines. Then, along with the development of increasingly advanced technology, it will facilitate learning and socialization, namely with this Quiz Game. This study intends to create a Covid-19 quiz educational game developed with quizzes of various levels for users to achieve, with research subjects people in general. This game uses the SDLC (System Development Life Cycle) method with the waterfall method. SDLC waterfall is one of the many system development methods that is quite popular and is often used by system developers, web-based applications, information systems, but not only that SDLC waterfall can also be applied in various other software, one of which is in the development game applications, especially educational games. The test results will use blackbox in the quiz educational game, and run without any errors or defects. The results of the validity and reliability test of the 70 people’s questionnaire are respectively valid and consistent/reliable. It can be concluded that the development of this game can help to educate the Indonesian people regarding Covid-19.